Effect of Chromoendoscopy Filters on Visualization of KTP Laser–Associated Tissue Changes: A Cadaveric Animal Model. (16th January 2018) - Johnson, Christopher M.; Pate, Mariah B.; Postma, Gregory N.
Abstract : Standard KTP laser (potassium titanyl phosphate) wavelength‐specific protective eyewear often impairs visualization of tissue changes during laser treatment. This sometimes necessitates eyewear removal to evaluate tissue effects, which wastes time and poses safety concerns. The objective was to determine if "virtual" or "electronic" chromoendoscopy filters, as found on some endoscopy platforms, could alleviate the restricted visualization inherent to protective eyewear. A KTP laser was applied to porcine laryngeal tissue and recorded via video laryngoscopy with 1 optical (Olympus Narrow Band Imaging) and 8 digital (Pentax Medical I‐scan) chromoendoscopy filters. Videos were viewed by 11 otolaryngologists wearing protective eyewear. Using a discrete visual analog scale, they rated each filter on its ability to improve visualization, . No filter impaired visualization; 5 of 9 improved visualization. Based on statistical significance, the number of positive responses, and the lack of negative responses, narrow band imaging and the I‐scan tone enhancement filter for leukoplakia performed best. These filters could shorten procedure time and improve safety; therefore, further clinical evaluation is warranted.